2022
DOI: 10.1111/adj.12910
|View full text |Cite
|
Sign up to set email alerts
|

Examination of canalis sinuosus using cone beam computed tomography in an Australian population

Abstract: Background: Canalis sinuosus (CS) and its relationship with adjacent teeth is relevant for surgery in the anterior maxilla. Therefore, the aim of this study was to report the prevalence, characteristics and variations of CS. Methods: Cone beam computed tomography (CBCT) scans of the anterior maxilla of 201 patients were reviewed. CS and the adjacent teeth were analysed by age, gender and scan resolution, using analysis of variance, Chi-squared and Fisher's exact tests. The widest and narrowest diameters of CS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 46 publications
7
9
3
Order By: Relevance
“…It looks more correct to think of ABCS as a variation in the anterior maxilla when it is wide, for example wider than 1 mm in diameter. The current study reports no correlation between the age and presence of ABCS which is concordant with previous studies [12,13,15,17,19,20].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It looks more correct to think of ABCS as a variation in the anterior maxilla when it is wide, for example wider than 1 mm in diameter. The current study reports no correlation between the age and presence of ABCS which is concordant with previous studies [12,13,15,17,19,20].…”
Section: Discussionsupporting
confidence: 93%
“…The increase in visibility of ABCS in recent years, has already been linked to the widespread use of CBCT in dentistry and high resolution and detail it provided [23]. Besides that, although we detected more ABCS per scan as the size of voxels decreased in our study, Yeap et al [20] did not nd a signi cant difference between voxel sizes in terms of the number of canals. Their study included 95.5% of scans with small voxel sizes under 200 µm.…”
Section: Declarationscontrasting
confidence: 61%
See 2 more Smart Citations
“…Yeap et al [ 32 ] also conducted a study to examine the CS in the Australian population using CBCT, and they reported at least one CS on 198 scans with 98.5% prevalence. The high prevalence reported in their study is in accordance with our results.…”
Section: Discussionmentioning
confidence: 99%